2020
DOI: 10.1016/j.jprot.2019.103580
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative quantitative proteomics of osmotic signal transduction mutants in Botrytis cinerea explain mutant phenotypes and highlight interaction with cAMP and Ca2+ signalling pathways

Abstract: (SPS) for financial support of proteomics equipment. They thank Adeline Simon for helping with enrichment studies. AUTHOR CONTRIBUTIONS STATEMENT JK designed and performed all experiments, assisted by MD for the proteomics workflow. MZ performed proteomic data analysis and corresponding statistics. AS performed in silico cluster analysis and functional enrichment studies. SF and MZ conceived the initial project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…To detect TaFRQ LUC oscillations at protein levels, TaFRQ LUC reporter strains were subjected to a time-course experiment in GYEC+ peas culture media, for which samples were taken every 4 hr for 52 hr, following a time-course protocol similar to the ones in Neurospora ( Larrondo et al, 2015 ), except that T. atroviride cultures were kept in DD, and reset by a strong LP to mimic an LL to DD transition. Proteins were extracted as described by Kilani et al, 2020 . Protein concentration was determined by the Bradford method, using the Bio-Rad Protein Assay (Bio-Rad Laboratories, Inc, CA).…”
Section: Methodsmentioning
confidence: 99%
“…To detect TaFRQ LUC oscillations at protein levels, TaFRQ LUC reporter strains were subjected to a time-course experiment in GYEC+ peas culture media, for which samples were taken every 4 hr for 52 hr, following a time-course protocol similar to the ones in Neurospora ( Larrondo et al, 2015 ), except that T. atroviride cultures were kept in DD, and reset by a strong LP to mimic an LL to DD transition. Proteins were extracted as described by Kilani et al, 2020 . Protein concentration was determined by the Bradford method, using the Bio-Rad Protein Assay (Bio-Rad Laboratories, Inc, CA).…”
Section: Methodsmentioning
confidence: 99%
“…UPS2 contains a mixture of 48 human proteins at six different molar concentrations, where there are eight proteins of different molecular masses present at each concentration level. Multiple studies have found strong positive correlations between the expected and observed relative abundances of UPS2 proteins [ 7 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, in all cases, there was a need for massive amounts of UPS2 to carry out quantification (e.g., up to 3–10 µg per mass spectrometry run), which is a constraint if the goal is to analyze large cohorts.…”
Section: Introductionmentioning
confidence: 99%